Kerjasama Dinas Kearsipan dan Perpustakaan Kota Bandung dengan KPK RI dalam Agenda Anti Korupsi: Mewujudkan Kesejahteraan Masyarakat Melalui Pojok ACLC (Anti Corruption Learning Center) - Fisalsabila, Meskia Tania; Silvana, Tine (Universitas Negeri Padang, 2023)
Collaboration within the library sector has become a vital initiative to address the limitations of public libraries in providing information, particularly regarding anti-corruption resources. To bridge this information gap, KPK RI initiated a partnership with the Bandung City Archives and Library Office. This study aims to explore the role of this collaboration in promoting community welfare through the establishment of the Anti-Corruption Learning Center (ACLC) Corner. A qualitative research methodology with descriptive analysis was employed, utilizing data collection techniques such as interviews, observations, and literature reviews. The research findings reveal that the inception of the ACLC Corner is geared towards promoting anti-corruption literacy and education by disseminating knowledge about the dangers of corrupt practices and preventive measures from an early age. The program aspires to equip the community with comprehensive insights into corruption and encourages active participation in its prevention, with a focus on reducing corruption cases, particularly in Bandung. Although the program is currently a collaborative effort between the two entities, it is expected to, in the short term, enhance public understanding of corruption and its ramifications within the community of Bandung